2022
DOI: 10.3389/fbioe.2022.920639
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing synthetic biology for sustainable biomining with Fe/S-oxidizing microbes

Abstract: Biomining is a biotechnological approach where microorganisms are used to recover metals from ores and waste materials. While biomining applications are motivated by critical issues related to the climate crisis (e.g., habitat destruction due to mine effluent pollution, metal supply chains, increasing demands for cleantech-critical metals), its drawbacks hinder its widespread commercial applications: lengthy processing times, low recovery, and metal selectivity. Advances in synthetic biology provide an opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, the accumulation of chemical pesticides is considered one of the most problematic issues, which in turn directly influences human health. Some studies have indicated that exposure to pesticides during pregnancy negatively affects fetal growth and, in some cases, may lead to fetal deformities [3] and [4]. [5], indicated that the consumption of chemical pesticides in the world was estimated as two million tons during the past four decades, and Europe constitutes 50% of global consumption, while the United States represents 25% and the rest of the world 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the accumulation of chemical pesticides is considered one of the most problematic issues, which in turn directly influences human health. Some studies have indicated that exposure to pesticides during pregnancy negatively affects fetal growth and, in some cases, may lead to fetal deformities [3] and [4]. [5], indicated that the consumption of chemical pesticides in the world was estimated as two million tons during the past four decades, and Europe constitutes 50% of global consumption, while the United States represents 25% and the rest of the world 25%.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Nonetheless, the utilization of Acidithiobacillus in biomining presents several challenges that need to be addressed, such as excess sulfuric acid generation, a long growth cycle, a low biomining rate, and a lack of selectivity when releasing metals. 10 biology offers promising solutions to these problems. Recent studies have demonstrated that genetically engineered Acidithiobacillus strains exhibit significantly improved biomining performance.…”
Section: Introductionmentioning
confidence: 99%
“…They are capable of oxidizing iron and/or sulfur to derive energy and fix carbon dioxide as their primary carbon source . Members of Acidithiobacillus are well-known for their efficient biomining capabilities and are harnessed to recover metals and rare earth elements from a variety of sources, such as ores, mine tailings, electric wastes, and spent batteries. Their highly adaptive nature and ability to thrive under extreme conditions make them promising candidates for bioremediation and biomining applications and future space biomining missions. , Nonetheless, the utilization of Acidithiobacillus in biomining presents several challenges that need to be addressed, such as excess sulfuric acid generation, a long growth cycle, a low biomining rate, and a lack of selectivity when releasing metals . Synthetic biology offers promising solutions to these problems.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental release of bioengineered organisms is increasingly being suggested for a variety of applications, including bioremediation 1 , biosequestration 2 , bio-mining 3 , environmental biosensing 4 and conservation 5 . The objectives of many environmental release applications shift the goals of biocontainment from preventing organism spread outside of closed spaces (e.g., laboratories or bioreactors) to managing the persistence of engineered organisms and their genetic material in open, dynamic environments.…”
mentioning
confidence: 99%